Ideologi dalam Wacana Perlawanan Postingan Instagram Tuntutan 17+8: Analisis Linguistik Fungsional-Sistemik - Risnawati Risnawati; Anang Santoso; Martutik (Universitas Muhammadiyah Magelang, 2026)
This research stems from the growing phenomenon of social resistance expressed through digital media, particularly on Instagram. The “Tuntutan 17+8” post offers a compelling example of how language is used to voice ideology and negotiate power relations in virtual spaces. The purpose of this study is to describe the forms of ideology represented in this resistance discourse and to explain how linguistic functions shape its ideological meaning. The study applies a Systemic Functional Linguistics (SFL) approach with a qualitative descriptive method. Data from posts and comments were analyzed using Halliday’s three metafunctions: ideational, interpersonal, and textual. The findings reveal that the ideational function represents social experiences through criticism of injustice and expressions of solidarity; the interpersonal function shows how attitudes, emotions, and empathy create a sense of closeness between writers and readers; and the textual function organizes the message to strengthen the meaning of resistance. These findings suggest that language in digital spaces functions not only as a means of communication but also as a medium for negotiating ideology and building collective social awareness.